2010
DOI: 10.1111/j.1095-8649.2010.02710.x
|View full text |Cite
|
Sign up to set email alerts
|

Life history of a simultaneously hermaphroditic fish, Diplectrum formosum

Abstract: Sand perch Diplectrum formosum were collected in the Atlantic Ocean waters off the south-eastern U.S. for life history analyses between April 2001 and July 2004 and ranged in size from 63 to 236 mm standard length (L(S)) and 0-8 years of age. Diplectrum formosum are simultaneous hermaphrodites that reach 50% sexual maturity at 12.2 months and 122.8 mm L(S) for testicular tissue and 13.6 months and 129.3 mm L(S) for ovarian tissue. The gonad contains ovarian and testicular tissue separated by a thin basement me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…The main characteristic of this genus is the presence of an accessory reproductive structure (ovarian sinus) whose function is to store hydrated oocytes. This structure has been reported for D. rostrum , D. pacificum , D. bivittatum and D. formosum (Bortone, , ,b; Bubley & Pashuk, ; Touart & Bortone, ). The species D. radiale is found inhabiting coastal and estuarine areas of the eastern and north‐east coasts of South America at depths of up to 60 m, may reach 250 mm in total length and feeds on crustaceans and small fish, playing an important role in the structure of ecosystems (Bortone, ; Carpenter, ).…”
Section: Introductionsupporting
confidence: 74%
See 4 more Smart Citations
“…The main characteristic of this genus is the presence of an accessory reproductive structure (ovarian sinus) whose function is to store hydrated oocytes. This structure has been reported for D. rostrum , D. pacificum , D. bivittatum and D. formosum (Bortone, , ,b; Bubley & Pashuk, ; Touart & Bortone, ). The species D. radiale is found inhabiting coastal and estuarine areas of the eastern and north‐east coasts of South America at depths of up to 60 m, may reach 250 mm in total length and feeds on crustaceans and small fish, playing an important role in the structure of ecosystems (Bortone, ; Carpenter, ).…”
Section: Introductionsupporting
confidence: 74%
“…The simultaneous occurrence of postovulatory follicles at different stages and the ovarian sinus filled only with hydrated oocytes found in the present study corroborate the hypothesis of oocyte storage, indicating that the hydrated oocytes were stored in the accessory reproductive structure of D. radiale for at least 24 hr. To date, no atretic oocyte has been recorded in the ovarian sinus of Diplectrum spp., contradicting the theory of oocyte resorption (Bubley & Pashuk, ; Touart & Bortone, ). However, in the present study, atretic hydrated oocytes were found within the ovarian sinus, revealing that the villi‐like projections may also reabsorb the unspawned oocytes, as stated previously by Bortone (), or that atretic hydrated oocytes would be eliminated in the next spawning event.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations